SPATIAL DISTRIBUTION OF VEGETATION IN TYSHKANTAU RIDGE (ZHETYSU ALATAU MOUNTAINS) (Experimental biology, 2016)
Spatial distribution of vegetation in Tyshkantau ridge (southern range of Zhetysu Alatau mountains) is described. Crop wild relatives and their abundance are revealed in plant communities.
Keywords: vegetation; spruce forest; pastures; dominants; crop wild relatives.